Cape Verde's Infrastructure : A Continental Perspective - Briceno-Garmendia, Cecilia M.; Benitez, Daniel Alberto (World Bank, Washington, DC, 2017)
The Africa Infrastructure Country Diagnostic (AICD) has gathered and analyzed extensive data on infrastructure in more than 40 Sub-Saharan countries, including Cape Verde. The results have been presented in reports covering several sectors—ICT, irrigation, power, transport, water and sanitation— and various policy areas, including investment needs, fiscal costs, and sector performance. This report presents the key AICD findings for Cape Verde, allowing the country’s infrastructure situation to be benchmarked against that of its African peers. Given that Cape Verde is a relatively well- off middle-income country, its performance will be benchmarked against that of other middle-income countries in Africa. Detailed comparisons will also be made with immediate regional neighbors in the Economic Community of West African States (ECOWAS), and where relevant, with other island states that face a similar set of infrastructure challenges.